2016
DOI: 10.15171/jcs.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Understanding of the Concept of Self-Esteem: a Qualitative Study

Abstract: Introduction: The concept of self-esteem has several definitions in different paradigms. Nursing has a unique and combined paradigm; therefore it is necessary to explore nursing students’ understanding of the concept of self-esteem. The present study aimed to discover the extent and characteristics of the concept of self-esteem from the perspective of Iranian nursing students through a qualitative approach. Methods: This study was conducted using the conventional content analysis method with the participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
2
20
3
Order By: Relevance
“…Self -esteem is defined as the degree to which individuals' value themselves (Reber and Reber, 2001). It is an outcome of mixed personal and professional values, a rational to maintain commitment to identity and professional standards, and act as a protective mechanism of moral distress when value conflict is occurred (Zamanzadeh et al, 2016). There are few studies examined the direct relationship between verbal abuse and nurse's self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Self -esteem is defined as the degree to which individuals' value themselves (Reber and Reber, 2001). It is an outcome of mixed personal and professional values, a rational to maintain commitment to identity and professional standards, and act as a protective mechanism of moral distress when value conflict is occurred (Zamanzadeh et al, 2016). There are few studies examined the direct relationship between verbal abuse and nurse's self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Students might choose such a profession because they have a low self‐concept consistent with that image, or because they feel strongly that it is their calling. A qualitative study using Mruk's model with nursing students showed that self‐esteem was influenced by the value accorded to, and enthusiasm about, their education and profession (Zamanzadeh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 14 Self-esteem includes nursing student's sense of honour about themselves which can impact academic failure, dropping out, or vice versa (their academic achievements. 15 However, no study was found to be specifically on the need for clinical nursing educators’ awareness about their influence on students' self-esteem. Doing further studies in this field is recommended.…”
Section: Discussionmentioning
confidence: 99%